Blood flow distributions by microsphere deposition methods - Prinzen, Frits W. (2000)
The art and science of the use of deposition markers for the estimation of blood flow distributions throughout the body and within organs is reviewed. Development of diffusible tracer techniques started 50 years ago. Twenty years later, radioactive 15 micron microspheres became the standard marker. Early studies on small animals, fetal sheep in 1967 and rats in 1976, provoked much of the technical development. Needs for avoiding the use of radioactivity, for having long lasting labels, and for providing higher spatial resolution, are driving the continuing exploration of newer techniques using colored and fluorescent microspheres and molecular deposition markers. Strengths and weaknesses of the various methods are compared.